Answer:
no this graph is not represent a function.
Answer:
<h2>-x²+4x +6</h2>
Step-by-step explanation:
Given f(x)=4x+1 and g(x)=x²-5
(f-g)(x) is derived by taking the difference of both functions
(f-g)(x) = f(x)-g(x)
(f-g)(x) = 4x+1 - (x²-5)
(f-g)(x) = 4x+1-x²+5
(f-g)(x) = -x²+4x +6
This gives the requires expression
Answer
It's B
Step-by-step explanation:
It organizes the years from 1-6 and keeps the money consistent with the years
63 = 9k
divide by 9 on each side to get k by itself
k = 7
Answer:
B
Step-by-step explanation:
4 (x - 7) - 2 (x + 1) = 10
x = 10
B. -2 (x - 7) + (x + 1) = 5
x = 10
your equation is equivalent to B!